The predictive ability of the STarT Back Screening Tool in a Danish secondary care setting - Morsø, L.; Kent, Peter; Manniche, C.; Albert, H. (Springer, 2014)
Introduction: The predictive ability of the STarT Back Tool (SBT) in secondary care settings has not been investigated. The aim of this study was to determine the SBT's predictive ability in a Danish secondary care setting and compare this to a Danish primary care setting. Methods: Poor clinical outcome at 6 months ( < 30 points on a 0-100 Roland Morris Disability Scale) was calculated in secondary care (n = 960) and primary care (n = 172) cohorts. The cohorts were stratified into SBT subgroups and estimates of additional risk for poor outcome were calculated [relative risk (RR), unadjusted and adjusted odds ratios]. The discriminative ability was determined using the area under the curve statistic. Results: In secondary care 69.0% and in primary care 40.2% had poor outcome on activity limitation. Although significant, the predictive ability of the SBT in secondary care (medium-risk RR 1.5, high-risk RR 1.7) was not as strong as in primary care (medium-risk RR 2.3, high-risk RR 3.5). Adjusting for episode duration and pain intensity only changed the predictive ability marginally in secondary care. The discriminative ability of the SBT was similar in both cohorts despite differences in the predictive ability. Conclusion The SBT had less predictive ability in a Danish secondary care setting compared to a Danish primary care setting for persistent activity limitation at 6 months follow-up. SBT-targeted treatment implications in secondary care were not investigated in this study.